Evaluation of Quality Assurance at Sub Primary Health Care Center in Basra City - Huda S. Juma, Hala S. Abdulwahid (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In the health context, the word “quality” often denotes a spectrum of desirable characteristics of health systems and, in particular, health care. Quality assurance programs are designed to investigate the effectiveness, efficiency, safety, and standards of health services and strategies and to identify measures for achievable improvements. A characteristic feature of quality assurance in health is that, with dynamic developments in medical practice required to stay in line with modern trends, the quality assurance system needs to be continually updated. Aims of The Study: To evaluate the quality assurance of sub-primary health care centers in Basra city, relative to their structure, process, and outcome. Methodology: A Descriptive study design was employed to evaluate the quality of primary healthcare with respect to structure, process, and consumer satisfaction, involving (60) clients and (10) sub-primary health Basra city for the period of October 15th 2021 through May 1st 2022. Non-probability “convenient” sample of (10) primary health care centers. Conclusion: The Ministry of Health and Environment with the collaboration of the Basra health directorate periodically monitors the primary healthcare centers in Basra City and guarantees that all of them, regardless of their classification as sub-primary healthcare centers. The Directorate of Public Health in Basra, which is responsible for the primary health care sectors in Basra, must distribute the medical staff according to health standards and indicators to ensure quality because there is a shortage of medical staff and in addition to a shortage of medical equipment because the primary care sub-centers cross the important part, especially in rural areas.